Enteroaggregative Escherichia coli Subclinical Infection and Coinfections and Impaired Child Growth in the MAL-ED Cohort Study. Issue 2 (February 2018) - Lima, Aldo A.M.; Soares, Alberto M.; Filho, José Q.S.; Havt, Alexandre; Lima, Ila F.N.; Lima, Noélia L.; Abreu, Cláudia B.; Junior, Francisco S.; Mota, Rosa M.S.; Pan, William K.-Y.; Troeger, Christopher; Medeiros, Pedro H.Q.S.; et al.
ABSTRACT: Objective: We evaluated the impact of subclinical enteroaggregative Escherichia coli (EAEC) infection alone and in combination with other pathogens in the first 6 months of life on child growth. Methods: Nondiarrheal samples from 1684 children across 8 Multisite Birth Cohort Study, Malnutrition and Enteric Diseases (MAL-ED) sites in Asia, Africa, and Latin America were tested monthly; more than 90% of children were followed-up twice weekly for the first 6 months of life. Results: Children with subclinical EAEC infection did not show altered growth between enrollment and 6 months. Conversely, EAEC coinfection with any other pathogen was negatively associated with delta weight-for-length ( P < 0.05) and weight-for-age ( P > 0.05) z scores between 0 and 6 months. The presence of 2 or more pathogens without EAEC was not significantly associated with delta weight-for-length and weight-for-age. The most frequent EAEC coinfections included Campylobacter spp, heat-labile toxin-producing enterotoxigenic E coli, Cryptosporidium spp, and atypical enteropathogenic E coli . Myeloperoxidase levels were increased with EAEC coinfection ( P < 0.05). EAEC pathogen codetection was associated with lower neopterin levels compared to those of no-pathogen control children ( P < 0.05). Mothers of children with EAEC coinfections had lower levels of education, poorer hygiene and sanitation, lower socioeconomic status, and lower breast-feeding rates compared to mothers of children in whom no pathogen was detected ( P < 0.05). Conclusions: These data emphasize the public health importance of subclinical EAEC infection in early infancy in association with other pathogens and the need for improved maternal and child care, hygiene, sanitation, and socioeconomic factors. Abstract : Supplemental Digital Content is available in the text